−4sin
2
x=4sin(
6
π
−x)sin(
+x),
1-4sin^{2}x = 4*\frac{1}{2}(cos(\frac{\pi}{6}-x-\frac{\pi}{6}-x)-cos(\frac{\pi}{6}-x+\frac{\pi}{6}+x)),1−4sin
x=4∗
1
(cos(
−x−
−x)−cos(
−x+
+x)),
1-4sin^{2}x=2cos2x-2cos\frac{\pi}{3},1−4sin
x=2cos2x−2cos
3
,
1-4sin^{2}x=2-4sin^{2}x-2*\frac{1}{2},1−4sin
x=2−4sin
x−2∗
1-4sin^{2}x-2+4sin^{2}x=-1,1−4sin
x−2+4sin
x=−1,
-1=-1.−1=−1.
ч. т. д.
если я правильно поняла то получиться х=0
−4sin
2
x=4sin(
6
π
−x)sin(
6
π
+x),
1-4sin^{2}x = 4*\frac{1}{2}(cos(\frac{\pi}{6}-x-\frac{\pi}{6}-x)-cos(\frac{\pi}{6}-x+\frac{\pi}{6}+x)),1−4sin
2
x=4∗
2
1
(cos(
6
π
−x−
6
π
−x)−cos(
6
π
−x+
6
π
+x)),
1-4sin^{2}x=2cos2x-2cos\frac{\pi}{3},1−4sin
2
x=2cos2x−2cos
3
π
,
1-4sin^{2}x=2-4sin^{2}x-2*\frac{1}{2},1−4sin
2
x=2−4sin
2
x−2∗
2
1
,
1-4sin^{2}x-2+4sin^{2}x=-1,1−4sin
2
x−2+4sin
2
x=−1,
-1=-1.−1=−1.
ч. т. д.
если я правильно поняла то получиться х=0